Remission of Obsessive-Compulsive Symptoms in Hypomanic Period in a Patient with Comorbid Bipolar Affective Disorder and Obsessive Compulsive Disorder: A Case Report (Annals of Medical Research, 2021)
None
Keywords: Bipolar Affective Disorders; Obsessive Compulsive Disorders; Comorbidity.